Hyperreflexia in Guillain Barre Syndrome: A Case Report (Journal of Bangladesh College of Physicians and Surgeons, 2015)
Guillain Barre Syndrome (GBS) is an immune mediated polyradiculoneuropathy classically characterized by acute ascending type of motor weakness of limbs with areflexia but in AMAN variant of GBS preserved or exaggerated reflex sometimes can occur. We report a 45 year old female patient who presented with acute flaccid quadriplegia, bilateral facial lower motor type nerve palsy and bulbar involvement, initial hyperreflexia of all four limbs and bilateral plantar extensor response 7 days following an attack of diarrhoea. Sensory and bowel bladder function was intact. She was treated with IV immunoglobulin and IV methylprednisolone. Nerve Conduction study (NCS) revealed AMAN variant of GBS. All reflexes disappeared on the 2nd day onward but returned on 21st day of illness when muscle power also improved. Follow up NCS confirmed regeneration of nerves of all four limbs. So in any patient presenting with acute quadriparesis GBS should be in the differential diagnosis even if there is preserved or exaggerated deep tendon reflexes.J Bangladesh Coll Phys Surg 2014; 32: 107-109